The equation of harmonic motion:
"x = A\\sin(\\omega t + \\phi_0)" , where "\\omega = \\sqrt{\\frac{k}{m}}" in case oscillating spring-mass system.
"\\phi_0" - initial oscillation phase (actually if it is, for example, "-\\frac{\\pi}{4}" we can rewrite it with cosine)
"\\dot x = A \\cdot \\cos(\\omega t + \\phi_0) \\cdot \\omega"
"E_k = \\frac{mv^2}{2} = \\frac{m\\dot x^2}{2} = \\frac{m(A\\omega \\cos(\\omega t + \\phi_0))^2}{2} = \\frac{m\\omega^2(A \\cos(\\omega t + \\phi_0))^2}{2} =\n\\frac{m\\frac{k}{m}(A \\cos(\\omega t + \\phi_0))^2}{2} \\Rightarrow"
"E_p = \\frac{kx^2}{2} \\Rightarrow"
As we can see expressions differ only in the initial phase (we can change the sine to cosine by changing the initial phase). with Pythagorean trigonometric identity:
"E_{mechanical} = E_p + E_k = \\frac{kA^2}{2} = const"
Comments
Leave a comment